Knowledge of medical school students on breast cancer and cervical cancer, and their prevention - Liszcz, Anna; Badowska-Kozakiewicz, Anna (Medical Studies/Studia Medyczne, 2015)
Introduction: Breast cancer and cervical cancer are the most common cancers in women. Early diagnosis of the disease can reduce mortality, so it plays an important role in the field of prevention measures. An important aspect is education, the aim of which is to provide information on the risk factors for cervical cancer and breast cancer, as well as the possibility of eliminating them from the life of women, but also shaping women’s need to perform regular diagnostics. Aim of the research : To evaluate the level of knowledge and its practical application in the private lives of medical school students. Material and method s: Two hundred and fifty female medical school students from different faculties were invited to take part in the investigation. The research used an original questionnaire by the authors. Results: The statistical analysis showed highly developed theoretical knowledge in the field of cancer prevention. The following risk factors of breast cancer were mentioned: genetic factors (87.6%) and age (65.2%); and risk factors of cervical cancer: numerous sexual partners (77.2%) and past viral infections (72%). Nevertheless, despite their knowledge on HPV influence on cervical cancer development, BRCA gene mutations, and other associated risk factors, 63.6% of students considered their knowledge unsatisfactory. Moreover, breast self-examinations were performed by 86% of respondents but only 44.5% had Pap tests performed. Conclusions : Despite the medical education of the respondents, it is highly recommended that actions aimed at promoting preventive diagnostics be intensified. Even though the students showed a high level of theoretical knowledge, it is crucial to increase and promote its practical application.